Impact of heart rate reduction on recurrence after catheter ablation of persistent atrial fibrillation. (4th February 2022) - Okada, M; Inoue, K; Tanaka, N; Masuda, M; Furukawa, Y; Hirata, A; Egami, Y; Watanabe, T; Minamiguchi, H; Miyoshi, M; Sunaga, A; Sotomi, Y; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Johnson & Johnson KK OnBehalf: OCVC Arrhythmia Investigators Background: Predicting heart rate (HR) after restoration of sinus rhythm (SR) remains one of the challenges when performing catheter ablation (CA) of persistent atrial fibrillation (AF). Purpose: To evaluate the association between pre-ablation HR during AF and post-ablation HR during SR, and whether the HR reduction is associated with AF recurrence. Methods: The analysis was performed from the EARNEST-PVI trial, a randomized controlled trial designed to assess a CA strategy for persistent AF, which was conducted in the Osaka region of Japan. After excluding patients with beta-blocker prescription, a total of 216 patients (median age, 67 years; 20% female; 23% long-standing persistent AF) with AF rhythm at baseline and SR at discharge were enrolled in this study. Baseline HR during AF and post-ablation HR during SR was measured on admission and at discharge using the 12-lead electrocardiograms, respectively. Results: There was a mild correlation between baseline HR (median 82 [interquartile range 72-95] bpm) and post-ablation HR (78 [48-117] bpm) (r = 0.27, p <0.001). Reduction in HR was positively associated with baseline HR (r = 0.79, p <0.001) and was negatively associated with post-ablation HR (r = - 0.37, p <0.001). During the follow-up of 1 year, 56 patients (25.9%) experienced AF recurrence. HR reduction had the higher diagnostic accuracy in predicting AF recurrence than HR at baseline and HR after CA (area under the curve, 0.625; 95% confidence interval, 0.557–0.690; p = 0.003). AF recurrence rate was significantly higher in 141 patients with smaller HR reduction (cut-off, <14bpm) than those with larger HR reduction (31.9% vs. 14.7%, p = 0.009). After adjustment of age, gender, long-standing persistent AF, and CA strategy, HR reduction of <14 bpm was a significant predictor of AF recurrence (hazard ratio, 2.32; 95% confidence interval, 1.20–4.51; p = 0.013). Conclusions: There was a mild correlation between HR during AF and HR after restoration of SR in patients underwent CA of persistent AF. HR reduction after restoration of SR predicted AF recurrence.